ANALISIS KESULITAN MEMBACA PADA SISWA KELAS V SD - Cahyani, Aulia Miftahul; Rukayati, Dwi Lestari; Riswari, Lovika Ardana (Universitas Tanjungpura, 2024)
The purpose of this research is to analyze reading difficulties in grade V students. the research method used in this research is descriptive qualitative method. The subject in this study is 1 grade V student who still cannot read properly in this high class, the student has the initials AK in the high class who cannot read. The place and time chosen by the researcher is located at SDN Widorokandang. The source of data obtained comes from students and homeroom teachers. In this study researchers used observation techniques, and interviews. The results showed that the reading difficulties experienced were difficulties in distinguishing the letters of the alphabet and the sounds on the symbols, resulting in these students not being fluent in reading and still spelling. When learning takes place, the student often makes noise in class and rarely pays attention to the teacher, when given a question by the teacher the student is only silent without answering it, even if he asks, the questions asked are not related to the material currently given by the teacher